Անձի ստեղծարարության հիմնախնդիրը հումանիստական հոգեբանության համատեքստում - Սոսե Խաչիբաբյան (ՀՀ ԳԱԱ հրատ.)
На данном этапе развития психологической науки вопросы креативности и творческого потенциала личности находятся в центре внимания разных исследователей. Эти темы исследовались представителями разных направлений психологии, и нужно заметить, что в контексте каждого направления креативность рассматривалась по-особому. At the current stage of development of psychological science the issues of a personality’s creativity and creative potential are within the focus of attention of the scientific community. These topics have been studied by representatives of different directions of psychology, and it is worth mentioning that in the context of each direction creativity has been examined differently.
Keywords: Psychology